BUILDING AN EFFECTIVE LEARNING ENVIRONMENT IN ISLAMIC RELIGIOUS EDUCATION: INSIGHTS FROM STUDENTS' PERSPECTIVES - Malihatun, Elih; R, Muhammad Dahlan (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Purpose: This study investigates how an effective learning environment in Islamic Religious Education contributes to student success. Method: Using a qualitative approach, data were collected through semi-structured interviews with 7 students at MTs. Al Furqon Kadudampit Sukabumi. Result: The findings reveal that fair grading, clear learning goals, and motivation through rewards are crucial factors in creating an engaging and successful learning environment. Conclusion: The study highlights the need for teachers to incorporate local wisdom and multicultural values into their teaching practices to foster a positive and inclusive classroom atmosphere